(untitled) (Research, Society and Development, 2023)
This article aims to problematize, in the light of the concepts of governmentality and care-of-self elaborated by Foucault, the effects of telework on the mental health of civil servants who exercise their profession in the modality of integral telework in a Court of Justice in the Northeast region of Brazil. This is qualitative research supported by the method of experimentation as understood in a Foucauldian perspective. In the production of data, the technique of individual interview was used, and as an instrument a sociodemographic questionnaire containing a trigger question, to give the participants, the opportunity to freely express their experiences in the home office. The results present both the (harmful) effects on mental health, such as the increase of anxiety and anguish resulting from the pressure to reach productivity goals, as well as the (positive) effects on the quality of life, such as the reduction of stress, the practice of physical activity and the expansion of family life. In this way, the study sheds light on the need for further research, in view of the global increase in the use of home office in the corporate universe.